Prospect of biodiesel production from chicken by products - Bibi Najlaa Bt., Buniamin Khan (Universiti Malaysia Sarawak (UNIMAS), 2009)
In recent years, the world has been triggered with the development of renewable energy sources that has a bright potential to replace the primary energy sources, which are the fossil fuels. One of the most famous renewable energy sources nowadays is the biodiesel. Biodiesel undergoes a simple transesterification process that separates the glycerine by-product from the biodiesel yielded. It is produced from renewable sources, such as, animal fats, vegetable oil, algae, recycled restaurant grease and used cooking oil. In the present study, the biodiesel was produced from chicken fats. Its performance was evaluated by using diesel engine model TNM – TDE – 700 and compared with conventional diesel. The biodiesel was divided into five blends; B5, B10, B15, B20 and B50. The performance was indicated in terms of speed, specific fuel consumption rate (SFC), brake horse power (BHP) and mechanical efficiency. Based on the calculation conducted and graphs constructed, B20 had the best performance compared to other blends. By using B20 as fuel, the highest speed achieved was (1515.67 rpm), highest brake horse power (35.902 kW), highest mechanical efficiency (62.11%) and the lowest specific fuel consumption (9.665 mL/kW). Hence, biodiesel of blend B20 can be considered as another optional renewable energy sources that the world can rely on instead of fossil fuels since the B20 performance is better than pure diesel. Biodiesel also contributes less to air pollution and can reduce the emissions of the greenhouse gases.